Identification of solar module behavior originating from backsheet failure - From lab studies to field tests - Buerhop, Claudia; Stroyuk, Oleksandr; Pickel, Tobias; Hauch, Jens; Peters, I. Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2021)
In this work we introduce a combination of spectral, imaging and electric lab and field tests that complement field I-V and power measurements and allow to track the insulation failures of the solar modules and associate various failure modes with different types of the module backsheets.
CRIS-Team Scopus Importer:2022-06-05
Keywords: backsheets; failure; monitoring data; yield impact